Two-wheeled LEGO EV3 Robot stabilisation control using fuzzy logic based PSO algorithm - M. F., Maharuddin; Normaniha, Abdul Ghani; N. F., Jamin (UTeM, 2019)
This paper presents a control system design to stabilise a two-wheeled Lego EV3 robot. This robot is developed based on the inverted pendulum. The mathematical modelling is derived based on this robot and using Euler Lagrange equation and represented in Simulink block diagram. The fuzzy logic controller is used to stabilise this robot with Particle Swarm Optimization algorithm for optimum performance of the system. The result of the fuzzy logic controller without optimisation is compared with the fuzzy logic controller with optimisation. Using the Simulink block diagram, the result of optimum tilt angle and control input signal are presented. The results show that the fuzzy logic controller with optimisation is able to improve the performance of the solution when compared to the fuzzy logic controller without optimisation.